Silicon‐Based Anodes: Recent Progress in Advanced Characterization Methods for Silicon‐Based Lithium‐Ion Batteries (Small Methods 10/2019). Issue 10 (15th October 2019) - Wu, Jingkun; Ma, Fei; Liu, Xiaorui; Fan, Xiayue; Shen, Long; Wu, Zhihong; Ding, Xiaoyang; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Zhong, Cheng
Abstract : The development of characterization methods is anticipated to greatly promote the upgrade of high‐performance lithium‐ion batteries (LIB) based on silicon (Si)‐based anodes. In article number1900158 by Fei Ma, Cheng Zhong and co‐workers, the recent advances and challenges in characterization methods for Si‐based LIBs are reviewed. With the insights provided by characterization methods, materials in Si‐based LIBs with improved design are expected to facilitate the future applications.